The Relationship Between Emotional Maturity And Conformity With Aggressive Behaviour Of Adolescents At Sma Negeri 04 Bengkulu City In 2024 - Pebrianti, Nesa; Darmawansyah, Darmawansyah; Tranado, Hengki (Universitas Dehasen Bengkulu, 2025)
Aggressiveness in adolescents can be influenced by internal factors and external factors. Internal factors, namely factors within the individual related to the mental process of adolescents, for example, do not have good emotional maturity. Emotions such as anger, frustration, and envy arise when the external stimulus received does not match the perception of the individual. This study aims to determine the correlation between emotional maturity and friend conformity with adolescent aggressive behavior at SMA Negeri 04 of Bengkulu City in 2024. The research method used is descriptive quantitative research with a cross sectional approach. Sampling technique using simple random sampling technique with the number of samples in this study 90 people representing all students at SMA N 04 Bengkulu City. The results of the univariate test analysis almost half of the respondents (25.6%) with poor emotional maturity, most of the respondents (68.9%) with high friend conformity, a small proportion of respondents (22.2%) often do aggressive behavior. The results of bivariate analysis obtained the results of emotional maturity (0.000) and friend conformity (0.021) with aggressive behavior. There is a correlation between emotional maturity and aggressive behavior of adolescents in SMA Negeri 04 of Bengkulu City. The researcher suggested that for SMA Negeri 04 of Bengkulu City the results of this study can be the basis for implementing guidance, coaching, and counseling activity programs on aggressive behavior.